Control Analysis of the Griya Jenggala Development Project using the Earned Value Method at PT Sarana Loka Almika in Kebayoran - Heni Nastiti; Denta Sawwath Suryana; Fattan Rahmat Firza Aulia; Muhammad Rayhan Ramsyahdira (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2023)
Project control is a structured effort to establish standards in accordance with the plan, design information systems, compare implementation with established standards, analyze potential deviations, and take corrective actions necessary to ensure the effective and efficient use of resources in line with the set targets. Each project has its own specific plan and schedule, determining the start and end time of the project, implementation methods, and resource allocation. Operational challenges often arise in project planning, such as resource shortages, improper allocation, delays, and other issues that may hinder the achievement of project goals as planned. This research utilizes a descriptive quantitative approach, which is a research method that describes the specific conditions of the project through the analysis of available data. This article will discuss the cost variance (CV) and schedule variance (SV) in the development of Griya Jenggala at PT. Sarana Loka Almika, evaluate the cost performance index (CPI) and schedule performance index (SPI) in the development of Griya Jenggala to assess its effectiveness, estimate the cost at completion (EAC) and estimated duration at completion (EAS) required to complete the Griya Jenggala project, as well as provide an estimation of potential profits or losses that may arise in the Griya Jenggala development project.